Factors Associated with Exclusive Breastfeeding Practice by Mothers who Work as Health Workers - Iswara, Salma 'Afindi; Utomo, Martono Tri; Ningtyas, Woro Setia (Pediomaternal Nursing Journal, 2022)
Introduction: Health workers play a notable role as "the significant others" in increasing maternal awareness and participation in fulfilling exclusive breastfeeding practices. In this case, female health workers tend to be the role models for other mothers in the community, including their child-feeding behavior. Based on the existing knowledge and work experience, female health workers should be able to breastfeed their babies exclusively. Yet several previous studies have shown the opposite result. This study aimed to analyze the factors associated with exclusive breastfeeding practice by mothers who work as health workers in Tulungagung Regency Public Health Centers. Methods: This study used a cross-sectional method. The sample in this study was 56 breastfeeding mothers who work as health workers in Tulungagung Regency Public Health Centers, selected by purposive sampling technique. Data were collected using a questionnaire and analyzed using the Chi-Square correlation test with a confidence limit of α=0.05. Results: Knowledge (p=0.091), attitude (p=0.094), and working shifts (p=0.185) did not correlate with exclusive breastfeeding practice. Husband's support (p=0.000) and family support (p=0.024) correlated significantly with exclusive breastfeeding practice. Conculusion: The breastfeeding mothers working as health workers who get a lot of support from their husbands and families tend to be confident to continue exclusively breastfeeding their babies despite returning to the workplace. The following researchers are expected to research other factors not examined in this study on a larger population and a more diverse health institution to determine how influential those factors are toward the exclusive breastfeeding practice.